Designing teacher evaluation systems : new guidance from the measures of effective teaching project - Kane, Thomas J.; Kerr, Kerri A.; Pianta, Robert C.; Measures of Effective Teaching Project (San Francisco, CA : Jossey-Bass, A Wiley Brand, 2014)
Definitive research for meaningful teacher evaluations All across America, in urban, suburban, and rural schools, teacher evaluation procedures are much-debated. Evaluation processes for teachers have varied over the years, and the usefulness of those processes to improve and assess the quality of a teacher's instruction has been questionable and often non-existent. Designing Teacher Evaluation Systems, New Guidance from the Measures of Effective Teaching Project provides you with original research from an extensive study that will help you rethink and redesign teacher evaluati.
Do Adults (FfT) and Students (Tripod 7Cs) Agree About Teaching?Conceptually Matching the Frameworks; Empirical Matching; The Special Case of Very Unruly Classrooms; Predicting Value Added, Happiness, Effort, and Inspiration; Value Added; Happiness and Effort in Class and College Inspiration; Achieving Order without Intimidation and Coercion; Maintaining Data Quality; Discussion and Implications; Do Adults and Students Agree about Teaching?; Predicting Value Added and Engagement; Maintaining Data Quality; Limitations; Conclusion; Notes.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Measures of Effective Teaching Project; Measures of Effective Teaching Project; Effective teaching; Teachers -- Rating of; Educational evaluation; EDUCATION / Administration / General; EDUCATION / Organizations & Institutions; Electronic books; Electronic books